EFEKTIVITAS PELAYANAN KESEHATAN DI RUMAH SAKIT PANCARAN KASIH MANADO - BUDO, ARWIS; TULUSAN, FEMMY; TAMPI, GUSTAAF (Sam Ratulangi University, 2020)
Quality Healthcare is one of the benchmarks of satisfaction that will affect the patient's desire to returnto the institution that provides effective health services. Based on the background of the purpose of thisresearch is to know how the effectiveness of health services at GMIM Pancaran Kasih Manado Hospital.This method of research is a qualitative study with a descriptive analysis approach the point describesthe opinion of the informant as it is in accordance with the research question. Research informants aredefined based on specific destination data sources or intentionally.The results showed that the ratio of health workers, doctors, nurses, midwives who are in the hospitalPancaran Kasih Manado with the number of patients treated is still very low so that many patientscomplain of the lags of medical action. Judging from the success aspects of achieving the target thattarget achievement targets that are contained in the vision and mission has not been fully realized, is thelack of human resources executing personnel such as doctors, nurses, midwives and hospital facilitiesand infrastructures that are not adequate. From the satisfaction aspect of the program'simplementation, the results showed that in general hospitalized patients expressed satisfaction with theservice provided by the hospital including the doctors and nurses.Keywords: effectiveness, service, health